The Effect of Education on Adolescents in Reducing the Stigma of Depression and Self Harm - Khadijah, khadijah; Caturini, Endang; Ariani, Dwi (Universitas Islam Jember, 2024)
Adolescence is referred to as the Storm and Stress period because their emotions are not yet stable. Globally, one in seven adolescents aged 10-19 years has a mental disorder. Negative stigma against depression, selfharm, and mental disorders is still strong in Indonesia, making sufferers feel isolated. Therefore, efforts are needed to reduce this stigma, one of which is through education via audiovisual. This study aim to determine the effect of education to adolescents in reducing the stigma of depression and selfharm. Pre-Experimental Research deign with One Group Pre-Post Test Design approach. Data were taken before and after the provision of educational interventions via audiovisual. The sample size was 70 respondents. This study measured stigma with the Self-Stigma of Mental Illness Scale Short Form questionnaire, 2) Mental Health Scale 3) General Help Seeking Questionnaire Vignete Version 4) Attribution Questionnaire Scale. The data will be analyzed using the Paired t-test (dependent t-test) or Wilcoxon. Results: There was a decrease in the average mental health scale of 8.72 with a p value of 0.000 (p<0.05). The average decrease inpublic stigma was 8.47 with a p value of 0.000 (p<0.05). Decreased mean level of self-stigma by 6.5 with p value 0.000 (p<0.05). Decreased mean level of help seeking by 12.93 with a p value of 0.000 (p<0.05). In conclusion, there is an influence of providing education about mental health, public level stigma, help seeking and self-stigma on adolescents.